2016
DOI: 10.1002/2015wr017728
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of turbulent super‐streamwise vortices based on observations of streaky structures near the free surface in the smooth open channel flow

Abstract: Long streamwise-elongated high-and low-speed streaks are repeatedly observed near the free surface in open channel flows in natural rivers and lab experiments. Super-streamwise vortex model has been proposed to explain this widespread phenomenon for quite some time. However, statistical evidence of the existence of the super-streamwise vortices as one type of coherent structures is still insufficient. Correlation and proper orthogonal decomposition (POD) analysis based on PIV experimental data in the streamwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…It indicates that the 10h order motions consist of two different types of smaller structures, hairpin packets, and Q4 events. This agrees with the phenomena reported by Zhong et al [12], Adrian and Marusic [22], Zhong et al [12] and Zhong et al [13] suggested a super-streamwise vortex model for the 10h order motions in open channel flows. The super-streamwise vortices rotate around the x axis.…”
Section: Wavelet Coherencysupporting
confidence: 92%
See 2 more Smart Citations
“…It indicates that the 10h order motions consist of two different types of smaller structures, hairpin packets, and Q4 events. This agrees with the phenomena reported by Zhong et al [12], Adrian and Marusic [22], Zhong et al [12] and Zhong et al [13] suggested a super-streamwise vortex model for the 10h order motions in open channel flows. The super-streamwise vortices rotate around the x axis.…”
Section: Wavelet Coherencysupporting
confidence: 92%
“…This two-energetic-mode feature of the pre-multiplied spectrum is similar to the results from other wall-bounded flows [15][16][17]. By the coherent structure classification in open channel flow [12,13], the h and 10h order motions can be classified as large-and very-large-scale structures.…”
Section: Wavelet Spectrumsupporting
confidence: 78%
See 1 more Smart Citation
“…Stream turbulence can influence vertical exchange in at least two ways, by controlling (1) the rate nutrients are delivered from the bulk stream to the streambed (or vice versa) and (2) mixing and transport of nutrients within the streambed (Figure a). In both cases, the vertical transport of mass (and momentum) is facilitated by eddies in the stream that are spatially coherent; that is, the positive or negative velocity fluctuations are spatially correlated (Grant & Marusic, ; Sinha et al, ; Vollmer et al, ; Zhong et al, ). At the sediment‐water interface, coherent turbulence manifests as sweep and ejection events, in which water parcels in the bulk stream with nutrient concentration C B (units of moles per cubic meter) sweep down to the interface, while water parcels near the interface with interfacial nutrient concentration C S (units of moles per cubic meter) are ejected into the bulk stream.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, del Álamo et al () analyzed the direct numerical simulation data and reported “wall‐detached/attached vortex clusters,” which have different properties as opposed to the hairpin vortex. Zhong et al () observed the existence of the coherent structure near the free surface.…”
Section: Discussionmentioning
confidence: 99%